Writing Oz pop: An insider's account of Australian popular culture making and historiography: An interview with Clinton J Walker - Hogan, T.; Beilharz, Peter (2012)
This interview-conducted by Peter Beilharz and Trevor Hogan with Clinton Walker over the course of three months (July to September 2011) between Melbourne and Sydney via email and Skype-explores the questions of Australian popular culture writing with, against, and of the culture industries themselves. Walker is a leading freelance Australian cultural historian and rock music journalist. He is the author of seven books, five about Australian music. He has been a radio DJ and TV presenter. He compiled and produced four double CD album collections of Australian music-Inner City Sound, Buried Country, Long Way to the Top, and Studio 22. He has been a key writer in several multi-media projects, including the Powerhouse Museum Real Wild Child exhibition and CD-Rom (1995) and ABC TV's hit documentary series/CD/DVD Long Way to the Top (2001). In 2006, a new US edition of his first book Inner City Sound (with soundtrack CD) was published. His Golden Miles: Sex, Speed and the Australian Muscle Car (2005) has been published in a revised edition in 2009. In 2012, his eighth book, The Wizard of Oz, will be published. Walker is currently writing with Beilharz and Hogan a book called The Vinyl Age: The History of Australian Rock Music, 1945-1995. The interviewers invited Walker to reflect critically on his 35-year 'career' as pop avatar, independent writer and critic in the post-war to post-modern Australian popular culture industries. Going from journalism to his path-finding books and television documentaries, the article traces this work's development both in personal terms and as a symptom of the broader cultural evolution, from the suburbs to pop to art and rock and back again; between London and the provincial cultures of Oz; from one-way American consumerism to local DIY egalitarianism, analogue to digital to global dialogue, youth culture to multi-culturalism, and from the putative low brow to the legimitization process itself of popular culture. © The Author(s) 2012.